Sheathing of the Endovaginal Ultrasound Probe: Is It Adequate? - Ronald Jimenez; Patrick Duff (Hindawi Limited, 1993)
The purpose of this prospective investigation was to compare two methods for sheathing of the endovaginal ultrasound-probe. The study was conducted over a 7-month period in 1991-1992. In the first half of the investigation, latex examination gloves were used to sheath the endovaginal probe; during the second half of the investigation, latex condoms were used. Following the ultrasound examination, the probes were inspected for gross contamination by the ultrasonographer. The sheaths were then tested for perforations by filling them with water to twice their usual volume and observing for leaks. Fifty unused gloves and condoms were similarly tested to determine the prevalence of preexisting defects. One hundred twenty-eight gloves and 102 condoms from patients were tested. Four gloves (3.1%, 95% C.I. 1.6-4.6%) and seven condoms (6.9%, 95% C.I. 4.4-9.4%) had perforations (NS). When the probe was covered by a glove, one instance of visible contamination occurred (0.78%, 95% C.I. 0-1.6%) compared with eight instances when the probe was covered with a condom (7.8%, 95% C.I. 5.2-10.4%, P < .007). The prevalance of preexisting defects in the 50 unused gloves was 2%, which is not significantly different from the prevalence in used gloves. There were no defects in the 50 unused condoms compared with 7 in the used condoms (P = .057). Visible contamination of the endovaginal probe with blood or genital tract secretions is more likely when condoms are used as sheaths. However, even gloves provide imperfect coverage of the probe, illustrating the need for thorough decontamination of the endovaginal instrument after each use.